(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Bacterial conjunctivitis is one of the most common ocular diseases that occurs worldwide and affects every age group and social strata. The disease Kaphaj Abhishyanda, which is due to vitiation of Kapha Pradhana Tridosha is comparable with this condition. In the management of bacterial conjunctivitis as per modern ophthalmology antibiotic and antihistaminic eye drops are prescribed. Because of recurrent use of antibiotics, chances of antibiotic resistance are increasing. The present study was planned to evaluate the management of same disease with Ayurvedic formulation. Ayurveda can provide better alternative treatment in such manifestation. Ayurvedic formulation mentioned in Ashtanga Sangraha on Kaphaj Abhishyanda was selected and the Bilwamuladi Kwatha was prepared for Aschyotana as mode of administration. 3 patients diagnosed with Kaphaj Abhishyanda were selected and given Bilwamuladi Kwatha Aschyotana 1 drop twice a day for 7 days. The assessment of symptoms was done before, during the treatment and after treatment. The Bilvamuladi Kwatha has Ushna Veerya and Kaphaghna properties, which helps in treating vitiated Kapha Dosha as well as Madhu and Shigru are known to be Chakshushya. Bilvamuladi Kwatha was found effective with significantly reducing symptoms of Kaphaj Abhishyanda and shows marked difference in bacterial culture and sensitivity testing of conjunctival smear, which is studied as objective parameter.